ANALISIS PENYELESAIAN KREDIT BERMASALAH MELALUI PENDIDIKAN DAN MITIGASI RESIKO PADA CU KELUARGA KUDUS PONTIANAK - Fransiskus Patra Rantomy; Herkulana Herkulana; Achmadi Achmadi (Universitas Tanjungpura, 2021)
AbstractThe main problems examined in writing this thesis are the implementation of basiceducation and further education for members, the credit risk mitigation process andthe management policies taken by the management in dealing with non-performingloans. took the object of Pontianak Kudus Family CU. The study used a qualitativemethodology. Qualitative data was obtained through interviews with the Manager andChairman of the Executive Board of the Kudus Family CU and three members whohad received member education from the Kudus Family CU. Non-partisanobservations and documentation were carried out on the implementation of educationand risk mitigation carried out by management. Data analysis was carried out byconducting narrative analysis on interview transcripts. In this study it can beconcluded: First, the education provided to members is very good with compulsoryeducation and further education according to the member's job segment. Second, riskmitigation has also been carried out not only from internal CUs, credit reserves arecarried out from the collectability system, as well as active and passive creditmonitoring. Third, the management policies that have been made include thedelegation of authority to terminate credit disbursement, the pre-credit educationpolicy is also carried out as a step to prevent non-performing loans as well as increasethe capacity of management human resources.Keywords: Risk Mitigation, Member Education And Management Policy